2019
DOI: 10.1159/000496401
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Restorative Materials Containing Preventive Additives in a Secondary Caries Model in vitro

Abstract: The incorporation of antibacterial agents into dental restorative materials is a promising strategy for secondary caries prevention. Previously, Carolacton affected Streptococcus mutans biofilm formation on composite materials in vitro. The present study evaluated secondary caries formation adjacent to Carolacton-containing composites and conventional restorative materials using an artificial biofilm model. Standardized cavities were prepared in bovine dentin-enamel samples (n = 175) and restored with various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…The available in vitro studies found no significant difference between various composites on the demineralization of surface and wall lesions. Some studies revealed that fluoride-containing materials (e.g., glass ionomers) reduce secondary caries progression [25][26][27]. A recent systematic review, of in situ studies, could not identify significant differences in secondary caries development in surrounding hard tooth tissues when different materials were used [28].…”
Section: Introductionmentioning
confidence: 99%
“…The available in vitro studies found no significant difference between various composites on the demineralization of surface and wall lesions. Some studies revealed that fluoride-containing materials (e.g., glass ionomers) reduce secondary caries progression [25][26][27]. A recent systematic review, of in situ studies, could not identify significant differences in secondary caries development in surrounding hard tooth tissues when different materials were used [28].…”
Section: Introductionmentioning
confidence: 99%
“…According to Isabel Metz et al, [(Metz et al, 2015)] there was much preventive measure taken after the primary restoration and yet there was prevalence of secondary caries 72.5% of the restoration failed within the first 2 years and most common restoration used during the primary restoration was composite According to Ivana Nedeljkovic et al [ (Nedeljkovic et al, 2020)] that there was a significant presence secondary caries prevalence with composite restoration and class 2 restoration. Franziska Hetrodt et al [ (Hetrodt et al, 2019)]. , have investigated that secondary caries formation is more prevalent in composite restoration and prepared in standardized cavities.Haitham Askar et al [(Askar et al, 2020)].…”
Section: Results and Discussion-mentioning
confidence: 99%
“…The available studies found no significant difference between various resin materials on the mineral loss of both surface and wall lesions. However, amalgam and fluoride-containing materials (e.g., glass ionomers) were able to reduce secondary caries progression in some studies [11,33,34]. It is unclear how these findings relate to clinical settings, e.g., patients using fluoridated toothpaste, etc.…”
Section: Do Different Materials Affect Secondary Caries Risk?mentioning
confidence: 99%
“…It is unclear how these findings relate to clinical settings, e.g., patients using fluoridated toothpaste, etc. Generally, large methodological heterogeneity applies to these in vitro studies, with various restorative protocols, methods to simulate caries, and techniques to evaluate mineral loss having been used [35][36][37].…”
Section: Do Different Materials Affect Secondary Caries Risk?mentioning
confidence: 99%